Voices of Innovation - AI : Fulfilling the Promise of AI in Healthcare - Marx, Edward W.; Dhingra, Sakshika; Papay, Frank; Mathur, Piyush (Productivity Press, 2025)
Innovation in healthcare has been both fast and slow.As an industry, we have clearly made great technological advancements, and yet we find ourselves behind peer industries when it comes to innovation with patient care, customer experience, augmented intelligence, virtual care, and cybersecurity. One reason for the lack of innovation velocity is the need for a universally adopted model or best practice framework. The time has come for Voices of Innovation - AI. Artificial intelligence is what some call the fourth transformative revolution in human history. Healthcare is among the many industries with significant opportunities for the use of AI and machine learning, as the convergence of technology and healthcare will result in significant innovation. This book is both practical and inspirational. Using the HIMSS model for innovation as the structural framework, Voices of Innovation - AI will showcase the great AI innovations being implemented across healthcare globally.With contributions from leading authorities in this field, this book will become the de facto resource for any organization seeking to leverage AI effectively. Loaded with numerous case studies and stories of successful innovation projects, this book helps the reader understand how to leverage AI to help fulfill the promise of technology in enabling superior business and clinical outcomes.
Keywords: Artificial intelligence -- Medical applications.; AI Innovation in Healthcare; elektronické knihy; electronic books